The Effect of School Climate and Coping Strategies on Expectancy for Success - Narulita, Gesha; Sugiyo, Sugiyo; Sunawan, Sunawan (Universitas Negeri Semarang, 2021)
School climate and coping strategies are components that help to determine students' expectancy for success. Bad school climate and coping strategies will result in little students who have high expectations for success in the future. This study aims to prove the previous statement, the extent of which the effect of the two components on students' expectancy for success. This correlational study involved 429 students consisting of 8 public high schools in Central Lampung. The finding proves that school climate has a significant effect on expectancy for success. In addition, coping strategies also have a significant positive effect on expectancy for success. The last finding shows that school climate and coping strategies bring a significant effect on expectancy for success. The results of this study are expected to draw implications for the importance of supporting students in establishing positive beliefs for their future success